Identification, Characterization and Stakeholder Analysis of Eco-tourism Destinations in Lake Toba Area - Paramitha, Natalia; Manik, Yosef; Halog, Anthony (AIBPM Publisher, 2019)
This study is aimed at identifying and characterizing the eco-tourism destinations in Lake Toba Area as well as mapping and analyzing the stakeholders involved in its value chain and governance. The study was conducted between January and April 2018 whereby a snowball sampling method was employed in identifying the eco-tourism destinations. A semi-structured questionnaire was used to record the characteristics of each destination point in terms of access, attraction, and amenities. Seventeen eco-tourism destinations located in seven regencies along Lake Toba Area have been identified. While access to these tourist destinations has been good enough, the destinations are lacking of attractions. The attractions are limited to natural panoramic views, such a pine forest and spectacular lake view without adequate activity options that can be done by tourist. In terms of supporting amenities, there are still many rooms that require attention and improvement. After that, the study continued by analyzing the role of stakeholders involved directly or indirectly in the operation, governance, and policy of eco-tourism destinations in the lake Toba region. The stakeholders are mapped and clustered based upon their power and interest into four categories: (i) key players, (ii) subjects, (iii) trend setter, and (iv) the crowd. It appears that owner/ administrator, regional tourism office, and several interrelated government offices, such as the Ministry of Tourism and the Ministry of Forestry and Environment are key players which possess high power and interest. On the other hand, private sector, mass media, and local communities are identified as dormant stakeholders or potential trend setters to some extent who possess high power but have low interest. The results of this study are essential inputs for further investigating the socio-economic impacts of the tourism-based development in the Lake Toba through Social Life Cycle Assessment methodology. Keywords: Lake Toba Area, eco-tourism, stakeholder analysis, life cycle assessment